SOSIALISASI PENGUJIAN KADAR TRIGLISERIDA TERHADAP KOAGULASI PROTROMBIN TIME PADA PASIEN DIABETES MELITUS TIPE 2 - Visensius Krisdianilo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Protrombin time (PT) test is conducted to identify abnormalities in blood clotting factors and assess the treatment that will be done to prevent bleeding. PT examination have several methods, one of wich, namely the method of photo-optic, wich check the protrombin time by detecting the turbidity that occurs as the value of protrombin time. An examination of the PT in influence by some of the things of which namely trigliserides as well as diabetes mellitus. High triglyceride levels will cause the serum to become turbid causing shortening of prothrombin time which is examined by the photooptic method, Based on the test results, it can be concluded that triglyceride levels with prothrombin time coagulation time, obtained the average triglyceride levels obtained 193 and the average coagulation time of 12.65 patients with type 2 diabetes mellitus. And also after this socialization activity all participants came to understand that there is a relationship between triglyceride levels with the time of coagulation of prothrombin time, which in this case is due to the turbidity caused by the tinnginya triglyceride levels in the blood.